The Role of Social Sciences and Philosophy in Shaping of the Sustainable Development Concept - Pawłowski, Artur (Problemy Ekorozwoju, 2008)
From Limits to Growth onwards, more and more people have come to understand that we only have one planet – one ”spaceship” – at our disposal. While the Earth’s geoecosystems possess natural selfregulatory mechanisms that allow the conditions necessary for life’s survival to be maintained, it is becoming clearer and clearer that this capacity is being compromised by human activity that is ever more clearly visible, and ever more markedly extending beyond what is necessary in meeting humanity’s basic needs. In this context, the questions needing answering concern: • the new political and social institutions required to ensure sustainability; • the initiatives required to direct human civilisation’s development (or survival) in the direction of sustainability; • the degree to which sustainability may be achieved by way of law; • the extent to which ”stick and carrot” will suffice in shaping pro-sustainability attitudes and behaviours; • the system of values to be invoked should the above emerge as inadequate; • the means of reconciling what is good for the individual with what is good for a given society (in line with the fact that market instruments are not able to do this, so other solutions need to be sought); • a convincing way in which to propagate the idea that intra- and inter-generational justice is necessary; • the separate problem (important in the shaping of pro-sustainability attitudes) of how to justify our duty to protect different elements of geoecosystems – should we do it for its own sake, or because it is essential to the quality of our existence? The threats to humankind result, not so much from the biological needs of our species, as from the characteristics and motivations of our civilisation. In connection with that, remedial measures need to be looked for in the sphere of human creativity, most especially in the development of the philosophical and social sciences, which should come up with a resonant idea for a socioeconomic order that ensures the sustainability essential if human civilisation is to go on.